2019
DOI: 10.1111/tpj.14235
|View full text |Cite
|
Sign up to set email alerts
|

Loss of fumarylacetoacetate hydrolase causes light‐dependent increases in protochlorophyllide and cell death in Arabidopsis

Abstract: Fumarylacetoacetate hydrolase (FAH) catalyses the final step of the tyrosine degradation pathway, which is essential to animals but was of unknown importance in plants until we found that mutation of Short-day Sensitive Cell Death1 (SSCD1), encoding Arabidopsis FAH, results in cell death under short-day conditions. The sscd1 mutant accumulates succinylacetone (SUAC), an abnormal metabolite caused by loss of FAH. Succinylacetone is an inhibitor of d-aminolevulinic acid (ALA) dehydratase (ALAD), which is involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 67 publications
(136 reference statements)
1
17
0
Order By: Relevance
“…Previously, we found that ROS marker genes such as APX2 , OXI1 , BAP1 and ZP were up-regulated before an occurrence of cell death in the sscd1 mutant 48 , so, we next investigated whether the repression of cell death in sscd1 by mutation of COI1 is correlated with the expression of these genes. Since the cell death phenotype of sscd1 seedlings that were grown under SD appeared on the 6th day 41 , 49 , therefore, we tested the expression of APX2 , OXI1 , BAP1 and ZP in seedlings grown under SD for 5 days.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we found that ROS marker genes such as APX2 , OXI1 , BAP1 and ZP were up-regulated before an occurrence of cell death in the sscd1 mutant 48 , so, we next investigated whether the repression of cell death in sscd1 by mutation of COI1 is correlated with the expression of these genes. Since the cell death phenotype of sscd1 seedlings that were grown under SD appeared on the 6th day 41 , 49 , therefore, we tested the expression of APX2 , OXI1 , BAP1 and ZP in seedlings grown under SD for 5 days.…”
Section: Resultsmentioning
confidence: 99%
“…Singlet oxygen is very unstable and difficult to detect within a cell 55 , however, some genes were specifically induced by singlet oxygen 40 . Recently, we found that the genes induced specifically by singlet oxygen 40 were up-regulated in sscd1 48 , suggesting that an effect of SUAC on Chl biosynthesis results in the generation of singlet oxygen in the sscd1 mutant. Furthermore, we found that treatment of Arabidopsis wild-type seedlings with SUAC activated the expression of JA-inducible genes (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations